2005
DOI: 10.1002/eji.200526157
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall glycosphingolipids ofSphingomonas paucimobilisare CD1d-specific ligands for NKT cells

Abstract: The current consensus on characterization of NKT cells is based on their reactivity to the synthetic glycolipid, a-galactosylceramide (a-GalCer) in a CD1d-dependent manner. Because of the limited availability of a-GalCer, there is a constant search for CD1d-presented ligands that activate NKT cells. The a-anomericity of the carbohydrate is considered to be an important requisite for the CD1d-specific activation of NKT cells. The gram-negative, lipopolysaccharide-free bacterium Sphingomonas paucimobilis is know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
232
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(242 citation statements)
references
References 48 publications
(77 reference statements)
6
232
1
1
Order By: Relevance
“…a-glucuronosylceramide from Sphingomonas sp. [26][27][28][29] and Ehrlichia sp. [28], a-galactosyldiacylglycerol from Borrelia sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…a-glucuronosylceramide from Sphingomonas sp. [26][27][28][29] and Ehrlichia sp. [28], a-galactosyldiacylglycerol from Borrelia sp.…”
Section: Introductionmentioning
confidence: 99%
“…a-glucuronosylceramide from Sphingomonas sp. [26][27][28][29] and Ehrlichia sp.[28], a-galactosyldiacylglycerol from Borrelia sp.[30], phosphatidylinositol mannoside from Mycobacterium sp.[31] and phosphoethanolamine [32] have recently been identified as ligands for iNKT cells, although all of these activate iNKT cells to a lesser degree than a-GalCer. Although lysosomal glycosphingolipid, isoglobotrihexosylceramide has been reported as a possible endogenous ligand for iNKT cells [28,33], a recent study argues against this possibility [34].…”
mentioning
confidence: 99%
“…Whereas the ability of some previously described ligands of microbial origin -Plasmodium (and Trypanosoma) glycosylphosphatidylinositol (GPI) and Mycobacterium phosphatidylinositol mannoside (PIM) -to activate iNKT cells has been questioned, recent work has rigorously demonstrated that GSL-1 from Sphingomonas and BbGL-II from Borrelia undoubtedly stimulate NKT cells in a CD1d-dependent manner [49,[63][64][65]. It remains to be determined whether direct recognition of these glycolipids by iNKT cells is responsible for the iNKT cell-dependent anti-bacterial activity noted during infection with these bacteria [49,63].…”
Section: Exogenous Inkt Cell Antigensmentioning
confidence: 99%
“…iNKT cells have been shown to directly recognize α-linked glycosphingolipids and diacylglycerol antigens that are expressed by bacteria such as Sphingomonas, Ehrlichia and Borrelia burgdorferi in a CD1d-dependent manner [49,[63][64][65] (Figure 1C). The biological response to these glycolipid antigens includes the production of IFNγ and IL-4 by iNKT cells.…”
Section: How Do Inkt Cells Get Activated? Cognate Recognition and Actmentioning
confidence: 99%
“…I will not relate these developments here in any detail, since the focus of this "historical feature" has been to recount the circumstances that led to our current definition of iNKT cells. Suffice it to say that there is now overwhelming evidence that iNKT cells can recognize a variety of microbial glycolipids [42][43][44], although the self glycolipids responsible for thymic selection of iNKT cells remain controversial [45,46]. It is obvious, however, that our ultimate understanding of the biological relevance of iNKT cells will depend to a large extent on the future identification of relevant endogenous and exogenous physiological glycolipid ligands.…”
Section: The Elusive Inkt Ligandmentioning
confidence: 99%